Control of the South American fruit fly in pear with natural-based products - Nunes, Marcelo Zanelato; Boff, Mari Inês Carissimi; Santos, Régis Sivori Silva dos; Franco, Cláudio Roberto; Rosa, Joatan Machado da (Federal University of Piauí, 2015)
This study aimed to assess, in laboratory conditions, the effect of andiroba oil (2L 100L-1), kaolin (7.5Kg 100L-1), azadirachtin (2.5L 100L-1), metidationa (100mL 100L-1) and distilled water (control) on the oviposition and mortality of adults of A.fraterculus in no-choice and free-choice tests. The experimental design was randomized with five treatments and 20 replicatesfor the no-choice test; and 15 replicates for the free-choice test. Fruits were immersed in each treatment solution, dried at room temperature and placed in pots with two couples of A. fraterculus (no-choice test) and in arenas with four couples along with a fruit that was previously immersed in water (free-choice test).Twenty-five days after infestation, fruits were dissecated and the number of larvae was recorded as well the number of pupae and adults. Only methidathion was effective on adults with mortality of 91.3% (P<0.05). There was no larval emergence and, consequently, pupae and adult development in fruits treated with andiroba oil and methidathion in both tests. Azadirachtin and kaolin did not present any effect on A. fraterculus. Andiroba oil was effective on the reduction of the infestation of pear fruits by A. fraterculus.